2021
DOI: 10.7717/peerj.11956
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale variation in a pristine montane cloud forest: evidence on high soil fungal diversity and biogeochemical heterogeneity

Abstract: Montane cloud forests are fragile biodiversity hotspots. To attain their conservation, disentangling diversity patterns at all levels of ecosystem organization is mandatory. Biotic communities are regularly structured by environmental factors even at small spatial scales. However, studies at this scale have received less attention with respect to larger macroscale explorations, hampering the robust view of ecosystem functioning. In this sense, fungal small-scale processes remain poorly understood in montane cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 131 publications
2
8
0
Order By: Relevance
“…Saprotrophs were among the abundant trophic modes with a high number of species with low prevalence (i.e., <25%) and low abundance per site (i.e., <10%) that were grouped as "other. " Dominance of saprotroph was reported earlier in tropical forests and coffee plantations suggesting that saprotrophs are key players in nutrient cycling (Looby and Treseder, 2018;Velez et al, 2021). Among the surveyed farms, we found that Ascomycotan Arachnotheca glomerata (Onygenaceae) and Basidiomycotan Geastrum spp.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Saprotrophs were among the abundant trophic modes with a high number of species with low prevalence (i.e., <25%) and low abundance per site (i.e., <10%) that were grouped as "other. " Dominance of saprotroph was reported earlier in tropical forests and coffee plantations suggesting that saprotrophs are key players in nutrient cycling (Looby and Treseder, 2018;Velez et al, 2021). Among the surveyed farms, we found that Ascomycotan Arachnotheca glomerata (Onygenaceae) and Basidiomycotan Geastrum spp.…”
Section: Discussionsupporting
confidence: 65%
“…This pathogen is not a menace in productive plantations and has rarely been reported in coffee plantations (Duong et al, 2020;Lu et al, 2022b). Apiotrichum and Fusarium were among the dominant genera, and this finding was previously reported in coffee plantations and montane forest (Arias and Abarca, 2014;Velez et al, 2021). Apiotrichum and Fusarium have been described as devastating pests affecting coffee production in Africa, where they usually infect mature trees and affect S2).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, only Trichoderma ceraceum was reported in this ecosystem, according to our review [103]. Velez et al (2021) [104] identified six morphotypes of Trichoderma in Mexican mountain cloud forests, but they did not identify these strains at the species level.…”
Section: Discussionmentioning
confidence: 67%
“…We expected that the local-scale soil climatic variables would play more critical roles than soil chemistry and vegetation in shaping bacterial and fungal diversity patterns and composition along the tropical elevational gradient, thereby supporting the Janzen’s hypothesis ( Frindte et al, 2019 ; Ma et al, 2022 ). Likewise, we expected that soil microbial communities would respond to the unique climate in cloud forests and hold a unique pattern in diversity and composition compared with other forests in the mountain ( Zimmermann et al, 2009 ; Velez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%